TRANSFORMATION OF THE SYSTEM OF THE INTERNATIONAL RELATIONS IN POST COVID-19 PERIOD - Karine Khojayan (International Journal of Innovative Technologies in Social Science, 2021)
The article analyses possible scenarios of global world order followed by the outbreak of COVID-19. It assesses to what extend the pandemic will impact the process of transformation of the system of international relations and discusses possible scenario of the global politics for post-COVID period. The article suggests that the expected outcome of the pandemic will be bi-polar world order, which will much differ from the system of the International Relations of Cold War period. The impact of COVID-19 on ongoing processes will be tangible. In the meanwhile, bearing in mind emerging neorealistic tendencies, enhancing role of states as pivotal actors of international system and current level of global inter-dependence, the international relations cannot return to the epoch where political realism had dominant position in global affairs. The article concludes that the pandemic will not drastically change the international order, but it will decently accelerate international processes, started years ago.